Travel Management Information System Employee Service at the Office of Industry and Trade of Provsu - Supianti P, Mahzuro; Ikhwan, Ali (Politeknik Ganesha Medan, 2023)
Technological developments and advances in science are currently developing rapidly, especially in the management of data that has used computers. The use of computers today is also used by individuals and groups that can facilitate their work. With the development of this information technology, there is an increasing need for an information system that can complete work in a systematic and efficient manner so as to facilitate the work of individuals or groups in the form of data management.The official trip itself is a work program at the agency in the form of a field activity that functions to find out and share experiences in accordance with the field of the program being carried out. With this official trip, every time a business trip is carried out, a trip report is needed to find out what activities have been carried out so as to produce a new work program for each existing agency. However, the BPK (Corruption Supervisory Agency) is often scrutinizing official travel itself, which is because every official trip is carried out, a budget will be given according to the stipulated budget, and the budget is quite large. Therefore every employee must also report official travel activities in a systematic and realistic manner.